Efferocytosis in health and disease - Doran, Amanda C. (Nat Rev Immunol, 2019)
The clearance of apoptotic cells by professional and non-professional phagocytes — a process termed ‘efferocytosis’ — is essential for the maintenance of tissue homeostasis. Accordingly, defective efferocytosis underlies a growing list of chronic inflammatory diseases. Although much has been learnt about the mechanisms of apoptotic cell recognition and uptake, several key areas remain incompletely understood. This Review focuses on new discoveries related to how phagocytes process the metabolic cargo they receive during apoptotic cell uptake; the links between efferocytosis and the resolution of inflammation in health and disease; and the roles of efferocytosis in host defence. Understanding these aspects of efferocytosis sheds light on key physiological and pathophysiological processes and suggests novel therapeutic strategies for diseases driven by defective efferocytosis and impaired inflammation resolution.